Will Religion Survive? A Critical Discussion of the Divergent Answers of two Atheists: Archaeologist David Lewis-Williams and Philosopher of Religion J.L. Schellenberg - Prozesky, Martin 1944- (2018)
Underlying this article are the questions of how to demarcate the phenomena to which the term 'religion' refers, and of how to differentiate between interpreting and explaining such phenomena - a matter to which David Chidester has offered guidance. These questions are approached by considering a different but closely related question: Does religion have a future, as answered in important recent books by two eminent scholars, both of them atheists, working in very different academic disciplines. These are the books of archaeologist, David Lewis-Williams, Conceiving God: The cognitive origins and evolution of religion (Lewis-Williams 2010) and philosopher of religion, J.E. Schellenberg's more recent work, Evolutionary religion (Schellenberg 2013). These works provide divergent answers to whether religion has a future - a divergence arising from different views about what constitutes religion. This article refers to their respective views, then provides a critical discussion of both, and ends by engaging, where relevant, with ideas in the work of David Chidester.
Keywords: brain science; Evolution; Explanation; future religion; Interpretation; unethical religion